Use of a specialized peptide-based enteral formula containing medium-chain triglycerides for enteral tube feeding in children with cerebral palsy and previous tube feeding intolerance on standard enteral formula: a prospective observational TolerUP study - Kansu, Aydan; Kutluk, Gunsel; Caltepe, Gonul; Arikan, Cigdem; Urganci, Nafiye; Tumgor, Gokhan; Erdogan, Simge (Frontiers Media Sa, 2025)
Objective Use of peptide-based formulas supplemented with medium chain triglycerides (MCTs) is considered a beneficial strategy to decrease the tube-feeding associated gastrointestinal tolerance. In children with cerebral palsy (CP), overall effects of enteral tube feeding as well as the utility of peptide-based specialized enteral formulas in those with gastrointestinal intolerance have not been extensively studied. This study aimed to evaluate the utility of enteral tube feeding via specialized peptide-based formula containing MCTs in children with CP in terms of gastrointestinal intolerance, anthropometrics, defecation characteristics and parental satisfaction with enteral formula.Methods Children with CP who received enteral tube feeding via specialized peptide-based formula containing MCTs were included in this prospective observational study. Anthropometrics (z scores for weight for age [WFA], weight for height [WFH], triceps skinfold thickness [TSFT] and mid-upper arm circumference [MUAC]), gastrointestinal intolerance symptoms, defecation frequency and stool patterns and formula satisfaction were recorded at baseline and during 6-month follow up.Results A total of 96 children with CP (mean +/- SD age: 5.6 +/- 3.2 years, 56.3% were boys) were included. Significant improvements were noted in MUAC, TSFT and WFH z scores at the 6th month visit. The rate of severe symptoms and the likelihood of Type-1/Type-2 (constipation) stool pattern were significantly decreased. Majority of parents were satisfied with the study formula.Conclusion Our findings revealed favorable efficacy and safety of using a specialized peptide-based formula containing MCT in provision of enteral tube feeding among children with CP in terms of improved anthropometrics, amelioration of gastrointestinal intolerance symptoms and normalization of bowel movements along with a high parental satisfaction.
Keywords: cerebral palsy; peptide-based formula; gastrointestinal intolerance; anthropometrics; parental satisfaction